Auto-psychological competence of future teacher of geography as a component of professional training - Byrka, Marian; Chubrei, Oleksandra (My University, 2019)
This article discusses auto-psychological competence as a system of characteristics that provide a high level of professional competence. Determination of the auto-psychological competence is connected with the fact that a person involved in professional activities should know his / her individual characteristics, abilities and inclinations and use them as means of realizing this activity. In addition, the auto-psychological competence acts as a factor contributing to the professional development of a person, where decisive importance is acquired to: need for self-organization in professional activities, independence and self-responsibility of the future teacher. The auto-psychological competence as a component of professional competence contributes to the conscious perception of the future teacher of their activities and, accordingly, allows them to manage the processes of self-development and self-education in professional activities, as well as provides a concentration of individual experience for solving professional problems.
Keywords: future teacher, professional training, professional development, components, content, auto-psychological competence